2018
DOI: 10.1111/vsu.12967
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term postoperative effects of administration of allogeneic blood products in 104 dogs with hemangiosarcoma

Abstract: Objective To determine the influence of administering allogeneic blood products (ABP) on the progression of hemangiosarcoma in dogs. Study design Multi‐institutional, retrospective study. Sample population One hundred four dogs with hemangiosarcoma that survived until postoperative discharge from the hospital. Methods Medical records of dogs that had been operated on for hemoangiosarcoma were reviewed for signalment, presence of a hemoabdomen, presence of metastatic disease, and whether the dog had received ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…In the present study, median StoC was 20 days; this is in line with a recent study by Finotello et al, 31 whereas two studies reported shorter times 1,25 . This relatively long interval may be due to several reasons.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, median StoC was 20 days; this is in line with a recent study by Finotello et al, 31 whereas two studies reported shorter times 1,25 . This relatively long interval may be due to several reasons.…”
Section: Discussionsupporting
confidence: 92%
“…In dogs, hemangiosarcoma (HSA) is a common and aggressive cancer of vascular origin. The spleen is the most common primary site, with nearly 50% of dogs having evidence of metastatic disease at presentation 1,2 . Splenectomy as the sole treatment modality is considered palliative; the addition of adjuvant doxorubicin‐based chemotherapy usually only increases the average survival time by 2–4 months 3–5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, transfusion related immunomodulation (TRIM) is a recently described consequence of allogenic blood product administration in man, although the exact mechanism by which this phenomenon occurs remains to be determined (33). TRIM may have as yet unknown implications in the veterinary field, and a recent study investigating long-term postoperative effects of administration of allogeneic blood products in dogs with hemangiosarcoma concluded that dogs administered allogenic blood products had a shorter disease-free interval than dogs that did not (34). For these reasons, avoidance of allogenic blood products may be of benefit in those patients that are able to be stabilized without the need for transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…12 A recent study in 104 canine patients with hemangiosarcoma indicated that administration of blood products and the presence of gross metastatic disease at the time of surgery shortened the disease-free interval, whereas administration of the Chinese herbal supplement Yunnan Baiyao prolonged the disease-free interval. 8 To confirm findings, immunohistochemistry was performed using endothelial cell immunomarkers that were selected due to their widely-accepted use in the diagnosis of hemangiosarcoma. CD31, also known as PECAM1 (platelet endothelial cell adhesion molecule 1), is a glycoprotein that is expressed on endothelial cells, platelets, and leukocytes and is involved many physiologic and pathologic pathways, including leukocyte migration, angiogenesis, maintenance of vascular integrity, and immunoregulatory roles in endothelial and hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%